Culture and application of conditionally reprogrammed primary tumor cells. (25th June 2020) - Zhong, Mengjun; Fu, Liwu
Abstract: Cancer is still a major public-health problem that threatens human life worldwide and further study needs to be carried out in the basic and preclinical areas. Although high-throughput sequencing technology and individualized precise therapy have made breakthroughs over the years, the high failure rate of clinical translational research has limited the innovation of antitumor drugs and triggered the urgent need for optimal cancer-research models. The development of cancerous cell lines, patient-derived xenograft (PDX) models, and organoid has strongly promoted the development of tumor-biology research, but the prediction values are limited. Conditional reprogramming (CR) is a novel cell-culture method for cancer research combining feeder cells with a Rho-associated coiled-coil kinase (ROCK) inhibitor, which enables the rapid and continuous proliferation of primary epithelial cells. In this review, we summarize the methodology to establish CR model and overview recent functions and applications of CR cell-culture models in cancer research with regard to the study of cancer-biology characterization, the exploration of therapeutic targets, individualized drug screening, the illumination of mechanisms about response to antitumor drugs, and the improvement of patient-derived animal models, and finally discuss in detail the major limitations of this cell-culture system.